Greco-Roman cities at the crossroads of cultures : the 20th anniversary of Polish-Egyptian conservation mission - Bakowska-Czerner, Grazyna; Czerner, Rafal (Archaeopress, 2019)
The ancient town discovered at the site of today's Marina el-Alamein (located on the northern coast of Egypt) developed from the 2nd century BC to the 6th century AD. It found itself at the crossroads of several civilisations: Hellenic, later replaced by Roman, and ultimately Christian, and was always strongly influenced by Egyptian tradition. A variety of cultures appeared and met here and grew in strength - then their significance weakened - but they always co-existed and influenced one another. The syncretism prevailing here is notable in the spheres of art, architecture, religion and worship. 2015 marked thirty years since the discovery of the remains of the ancient city, which, for many centuries, had been unknown to the world. The remains were found unexpectedly during the preparatory work for the construction of a modern tourist settlement on the Mediterranean coast, and the significance and extraordinary value of the discovery was immediately recognised. Now the ancient city, and the historic remains of its buildings, are gradually coming to light. The Jubilee was twofold, since 2015 marked also the 20th anniversary of the setting up of the Polish-Egyptian Conservation Mission, Marina el-Alamein. Throughout this time, both architectural and archaeological research have been carried out at the site, many discoveries have been made, numerous relics of historic building structures have been preserved, and conservation methods have been improved. In the jubilee year, researchers who work on archaeological sites and towns with a similar history and position in the ancient world in the realms of art and culture were invited to contribute to a scientific discussion and exchange of experiences. The contributors were representatives of different disciplines and research methodologies: archaeologists, architects, Egyptologists, specialists in religious studies, historians and conservators. The papers in the present volume encompass interdisciplinary reviews of both new and long-term studies carried out in various regions of the ancient world. The papers present research that was conducted in different regions ranging from ancient Mauritania, through Africa, Egypt, Cyprus, Palestine, Syria, as well as sites in Crimea and Georgia. The topography of cities, the architecture of public buildings, as well as houses and their décor -- architectural, sculptural and painted -- are presented. Religious syncretism and the importance of ancient texts are discussed. Studies on pottery are also presented. The volume includes studies on the conservation of architectural remains, sculpture and painting. Several articles are devoted to the study of Marina el-Alamein; others talk about ancient Alexandria, Deir el-Bahari, Hermopolis Magna, Bakchias, Pelusium, Kom Wasit, Berenike, Ptolemais, Apollonia, Palmyra, Nea Paphos, as well as Chersonesus Taurica and Apsarus